Best Buy in Public Health or Luxury Expense?: The Cost-effectiveness of a Pediatric Operating Room in Uganda From the Societal Perspective. Issue 2 (February 2021) - Yap, Ava; Cheung, Maija; Muzira, Arlene; Healy, James; Kakembo, Nasser; Kisa, Phyllis; Cunningham, David; Youngson, George; Sekabira, John; Yaesoubi, Reza; Ozgediz, Doruk
Abstract : Objective: To determine the cost-effectiveness of building and maintaining a dedicated pediatric operating room (OR) in Uganda from the societal perspective. Background: Despite the heavy burden of pediatric surgical disease in low-income countries, definitive treatment is limited as surgical infrastructure is inadequate to meet the need, leading to preventable morbidity and mortality in children. Methods: In this economic model, we used a decision tree template to compare the intervention of a dedicated pediatric OR in Uganda for a year versus the absence of a pediatric OR. Costs were included from the government, charity, and patient perspectives. OR and ward case-log informed epidemiological and patient outcomes data, and measured cost per disability adjusted life year averted and cost per life saved. The incremental cost-effectiveness ratio (ICER) was calculated between the intervention and counterfactual scenario. Costs are reported in 2015 US$ and inflated by 5.5%. Findings: In Uganda, the implementation of a dedicated pediatric OR has an ICER of $37.25 per disability adjusted life year averted or $3321 per life saved, compared with no existing operating room. The ICER is well below multiple cost-effectiveness thresholds including one times the country's gross domestic product per capita ($694). The ICER remained robust under 1-way and probabilistic sensitivity analyses. Conclusion: Our model ICER suggests that the construction and maintenance of a dedicated pediatric operating room in sub-Saharan Africa is very-cost effective if hospital space and personnel pre-exist to staff the facility. This supports infrastructure implementation for surgery in sub-Saharan Africa as a worthwhile investment. Abstract : Supplemental Digital Content is available in the text